Riti sacri nella Genova del Cinquecento: performances collettive e identitarie (Mantichora. Italian Journal of Performance Studies, 2020)
In 1500 in Genova, the sacred rites as well as collective and identitary performances. In that kind of society, the dramatic expression seems to relate to human activity ‘in general’.